Analysis of Aqueducts Subjected to Hydrostatic and Dynamic Loads Using 3D - Solid Modeling - Jitendra Singh Yadav; Sushas S Babu (Journal of Building Materials and Structures, 2020)
In many areas of developing countries, the access to fresh water is limited even today. Aqueducts are the major structures in water supply and diversion schemes when carrying the water over natural and artificial obstacles such as valleys, rivers, roads, railway lines, canals etc. During an earthquake, the effect of water sloshing on the walls of aqueduct and the resulting hydrodynamic forces is often neglected. In this study, the analysis is carried out for a single span elevated aqueduct using finite element analysis, in which the structure is discretized into smaller elements. The structure is modelled using solid elements in Staad Pro V8i software for different loads. The behavioral response of aqueduct structure subjected to hydrostatic loads and dynamic loads due to seismic ground excitation has been analyzed. It has been observed that the structure is more vulnerable to dynamic loads compared to hydrostatic loads. The effect of dynamic loads due to sloshing of water under seismic forces is predominant. The stresses induced by hydrodynamic loads are observed to be 2.4 times more than hydrostatic loads.